Clinical Features and Management of Drop Attacks in Menière's Disease. Special Emphasis on the Possible Occurrence of Vertigo After the Drop Attacks. Issue 8 (10th September 2021) - Lelonge, Yann; Karkas, Alexandre; Peyron, Roland; Reynard, Pierre; Convers, Philippe; Bertholon, Pierre
Abstract : Supplemental Digital Content is available in the text Abstract : Introduction: Tumarkin first described drop attacks (DA) in patients with a peripheral vestibular syndrome and speculated the role of a mechanical deformation of the otolith organs. We emphasized on the possible occurrence of vertigo/dizziness after a DA. In the light of the oculomotor examination of one patient right after the DA, we discussed on the mechanisms. We also described the management of DA. Material and Method: This study included patients with definite Menire's disease (MD) and at least one DA without associated neurological symptoms. Patients with vertigo/dizziness after the fall were not excluded. Results: Fifteen patients with MD complained of DA that was complicated either by severe head trauma (n = 1) or various fractures (n = 4). Seven patients complained of vertigo/dizziness after the DA. In one patient, DA occurred in the waiting room with a vertical illusion of movement immediately after the fall and a predominant down beating nystagmus that later changed direction. Follow up was favorable in all patients after oral medication alone (n = 7), chemical labyrinthectomy (n = 7) or vestibular neurotomy (n = 1). Conclusions: We suggest that a subset of patients with MD can complain of vertigo after a DA. We conclude on the possible occurrence of a vertical mainly down beating nystagmus in MD. Since this latter nystagmus is likely related to a semicircular canal rather than an otolith dysfunction, we discuss on the mechanisms of DA followed by vertigo/dizziness. Due to the risk of trauma in DA, chemical labyrinthectomy is a reasonable and effective option although spontaneous remission is possible.